2015
DOI: 10.2308/acch-51076
|View full text |Cite
|
Sign up to set email alerts
|

Big Data as Complementary Audit Evidence

Abstract: SYNOPSIS In this paper we argue for the use of Big Data as complementary audit evidence. We evaluate the applicability of Big Data using the audit evidence criteria framework and provide cost-benefit analysis for sufficiency, reliability, and relevance considerations. Critical challenges, including integration with traditional audit evidence, information transfer issues, and information privacy protection, are discussed and possible solutions are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
152
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(164 citation statements)
references
References 28 publications
1
152
0
11
Order By: Relevance
“…The consistent decline in fragmentation and increase in connectedness within the co-word network showed that the auditing discipline is becoming increasingly tight and cohesive (Kılıç et al, 2019;Varga, 2011 Advances in information technology, the rise of the real-time economy, and massive fraud scandals played a major role in the emergence of continuous auditing practices (Eulerich & Kalinichenko, 2018). Researchers have generally tended to study continuous auditing using XML-based accounting systems (Murthy & Groomer, 2004), in an internal auditing context (Gonzalez, Sharma, & Galletta, 2012), to determine whether it enhances financial reporting quality (Lee, Kang, Oh, & Pyo, 2014), to assess how to minimize the cost of continuous audit practices arising from the maintenance of a large dataset (Pathak, Chaouch, & Sriram, 2005;Pathak, Nkurunziza, & Ahmed, 2007), and to evaluate the incremental value of continuous auditing practice (Farkas & Murthy, 2014 ; the drivers of, and obstacles to, big data evolution in audits (Alles, 2015); the consequences of big data in accounting and auditing (Krahel & Titera, 2015); the impact of big data on audit evidence; and audit judgments and financial statement audits (Brown-Liburd, Issa, & Lombardi, 2015;Cao, Chychyla, & Stewart, 2015;Yoon, Hoogduin, & Zhang, 2015). It therefore seems to be a strong candidate for one of the future research avenues.…”
Section: Discussionmentioning
confidence: 99%
“…The consistent decline in fragmentation and increase in connectedness within the co-word network showed that the auditing discipline is becoming increasingly tight and cohesive (Kılıç et al, 2019;Varga, 2011 Advances in information technology, the rise of the real-time economy, and massive fraud scandals played a major role in the emergence of continuous auditing practices (Eulerich & Kalinichenko, 2018). Researchers have generally tended to study continuous auditing using XML-based accounting systems (Murthy & Groomer, 2004), in an internal auditing context (Gonzalez, Sharma, & Galletta, 2012), to determine whether it enhances financial reporting quality (Lee, Kang, Oh, & Pyo, 2014), to assess how to minimize the cost of continuous audit practices arising from the maintenance of a large dataset (Pathak, Chaouch, & Sriram, 2005;Pathak, Nkurunziza, & Ahmed, 2007), and to evaluate the incremental value of continuous auditing practice (Farkas & Murthy, 2014 ; the drivers of, and obstacles to, big data evolution in audits (Alles, 2015); the consequences of big data in accounting and auditing (Krahel & Titera, 2015); the impact of big data on audit evidence; and audit judgments and financial statement audits (Brown-Liburd, Issa, & Lombardi, 2015;Cao, Chychyla, & Stewart, 2015;Yoon, Hoogduin, & Zhang, 2015). It therefore seems to be a strong candidate for one of the future research avenues.…”
Section: Discussionmentioning
confidence: 99%
“…The next wave of automated audit technologies promises to have an even greater impact on the use of expert human auditors, and more importantly the development of new expert human auditors. This next wave is being driven largely by a focus on the use of data analytics and big data (Brown‐Liburd et al ., ; Cao et al ., ; Griffin and Wright, ; Vasarhelyi et al ., ; and Yoon et al ., ), the economic forces that are pushing for this data analysis capability to ‘make the audit more efficient’ (Alles, ), and the perceived ability of automated data analytics to solve many of the human bottlenecks in continuous auditing (Zhang et al ., ). Underlying all of these advances is a systematic effort to improve auditing by automating and alleviating the deficiencies of human judgement.…”
Section: Auditing and Assurancementioning
confidence: 99%
“…Which mirrored its effect on the methods and procedures of audit, although the audit objects in general are considered as one regardless the operating quality of manual or electronic data, but the audit procedures used by the auditor in conducting the tests may have been changed in response to the changing nature of each of the inputs elements and data operating processes and the nature of the output elements (Arens et al, 2012;Simkin et al, 2014). From here, governments in most countries are permanently seeking to develop rules and foundations and principles describe the mechanisms of correct and safe dealing of information, in particular those flows through the network in order to maintain this information from loss and damage, especially to deal (Abdullah & Fares, 2016), in both the public sector or private sector, especially in accounting information for its importance and its disclosure, and defining the roles (Yoon & Zhang, 2015) and duties that must be performed by the staff in order to achieve an appropriate level of security and protection for this information, and make them available when if needed for people and entities who have access authorization (Cavelty & Mauer 2016, NIACSS, 2012. The information flow across networks makes it difficult to follow up and verify that information (Romney et al, 2013), and in particular as long the complexity of networks is increased of and consequently such shall generates difficulties to find appropriate audit evidence (Simkin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%